2010
DOI: 10.1111/j.1751-1097.2010.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of a New Photodynamic Therapy with Glycoconjugated Fullerene

Abstract: When irradiated, fullerene efficiently generates reactive oxygen species (ROS) and is an attractive photosensitizer for photodynamic therapy (PDT). Ideally, photosensitizers for PDT should be water-soluble and tumor-specific. Because cancer cells endocytose glucose more effectively than normal cells, the characteristics of fullerene as a photosensitizer were improved by combining it with glucose. The cytotoxicity of PDT was studied in several cancer cell lines cultured with C(60)-(Glc)1 (D-glucose residue pend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Fullerenes are a class of closed-cage nanomaterials made solely from carbon atoms. Since photoinduced biochemical activity of fullerene carboxylic acid was first reported in 1993, [6] much scientific attention has been paid to the biological activity of fullerene derivatives [7][8][9][10][11] where their main biological applications include inhibiting the human immunodeficiency virus (HIV-1) protease, using potential anticancer agent, PS, and so forth. Especially, it has been systematically reviewed that the organically modified fullerene derivatives, as promising PSs are applied in PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes are a class of closed-cage nanomaterials made solely from carbon atoms. Since photoinduced biochemical activity of fullerene carboxylic acid was first reported in 1993, [6] much scientific attention has been paid to the biological activity of fullerene derivatives [7][8][9][10][11] where their main biological applications include inhibiting the human immunodeficiency virus (HIV-1) protease, using potential anticancer agent, PS, and so forth. Especially, it has been systematically reviewed that the organically modified fullerene derivatives, as promising PSs are applied in PDT.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the porphyrin and phthalocyanine derivatives having carboxylate or polyethyleneglycol groups were synthesized [14][15][16][17][18]. Yano and coworkers reported that glucopyranoside-conjugated porphyrin, chlorin and fullerene derivatives efficiently work as photosensitizers [19][20][21][22][23][24][25]. It is known that tumor has a property to accumulate glucose to the greater extent than normal tissue for the unnatural growth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared with radiotherapy, the activating light is non-ionizing and hence its effect on tissues without PS drug is not harmful [1][2][3]. Fullerene (C60), the third allotrope of carbon, are nano-scale carbon materials with unique photo-, electro-chemical, physical properties and low systemic toxicity [4][5][6][7]. In addition, C60 possess unique photochemical properties: under the irradiation of UV or visible light, C60 molecule is able to shift to the excitation triplet state and generate singlet and other active forms of oxygen [8,9].…”
Section: Introductionmentioning
confidence: 99%